Botho bo tlile pele: Reflections on Moral Decay in Post-1994 South Africa - Tondi, Pakiso (My University, 2018)
From reports in both print and electronic media, it has become obvious that South Africa is under a wave of unacceptable social behaviour. The situation poses a challenge for those who are custodians of the culture to reinstitute the traditional value systems that have over the years guided and characterized African communities. The crucial question here is: Which moral values should guide those assigned with the task of reconstructing the nation? In response, the article advocates for the retrieval and reinstatement of critical African traditional cultural value systems that can be employed to purge the country of anti-social behavioural tendencies such as the grab-and-run syndrome and others (list at least two others) that tend to undermine the fundamental human relations principles that are supposed to govern society and are meant to inculcate the spirit of love, compassion and respect for one‟s neighbour. This article aims to identify some of the prevalent anti-social behavioural modes in modern-day South Africa and their negative impact on the country‟s socio-economic development.
Published Article